Persentase Serangan Penyakit Layu Fusarium dan Pertumbuhan Vegetatif Tanaman Terong Ungu Akibat Pemberian Variasi Konsentrasi Trichoderma harzianum dengan Medium Beras - Nita, Dewi Afon; Julyasih, Ketut Srie Marhaeni; Manalu, Jean Nihana (Agrotrop : Journal on Agriculture Science, 2025)
Percentage of Fusarium Wilt Disease Attacks and Vegetative Growth of Purple Eggplant Plants Due to Variations in Trichoderma harzianum Concentration with Rice Medium . Purple eggplant ( Solanum melongena L.) is a vegetable commodity with a high consumption rate in Indonesia. This plant is included in horticultural crops that are widely cultivated in Indonesia. However, with high demand, problems often arise, such as Fusarium wilt disease. To overcome this disease caused by the pathogen Fusarium sp., this research was conducted to examine the ability of Trichoderma harzianum to inhibit the growth of the pathogen. The application of Trichoderma harzianum with varying concentrations (0%, 10%, 20%, 30%, 40%, and 50%) statistically proved to provide significant differences in suppressing the percentage of Fusarium wilt attacks, as shown by the one-way ANOVA test (p < 0.05). The use of Trichoderma at concentrations of 40% and 50% proved effective in providing full protection against Fusarium wilt disease, with a suppression rate reaching 100% after 28 days. The application of Trichoderma fungi statistically increased the number of plant leaves at 14 days after planting. However, based on a comparison between plants treated with Trichoderma and the control, the plant height in the treatment group was lower.